An Encephalocele presenting as CSF Rhinorrhea in an Adult Female: A Case Report - Hoti, Yaser Uddin (ADVANCES IN BASIC MEDICAL SCIENCES, 2019)
Encephalocele refers to the meningeal herniation, which may or may not be associated with brain parenchyma coming out. Encephalocele is very rare and occurs in almost 1 per 35,000 of all births. As this condition occurs due to embryological defect, so it occurs more frequently in infant with a mean age ranging between 15 and 21 months; making an encephalocele occurring in a relatively older individual a very infrequent entity. We present an extremely rare case of encephalocele occurring in a young obese female patient presenting to our department with a cerebrospinal fluid (CSF) rhinorrhea from the left nostril, which was dealt by endoscopic endonasal repair. We strongly advocate to keep the differential of encephalocele in CSF rhinorrhea and repair the encephalocele by endonasal endoscopic procedure.